ENHANCED LEARNING, EMPOWERING LIVES: A COMMUNITY- BASED LEARNING APPROACH FOR STUDENTS WITH SPECIAL NEEDS (Proceedings of International Conference on Special Education, 2025)
Community-Based Learning (CBL) integrates academic learning with community engagement, enabling students to apply theoretical knowledge to real-world projects while fostering civic responsibility, critical thinking, and personal growth. This concept paper explores CBL in the Service-Learning Project (SLP) initiative at MINDS Woodlands Gardens School (WGS), combining community service with curriculum learning to enhance inclusivity and support students with intellectual disabilities, including autism spectrum disorder (ASD) and high support needs. The initiative aligns with the Ministry of Education’s Values-in-Action (VIA) framework to promote empathy, civic responsibility, and 21st-century skills. The paper examines the application and impact of CBL in a Singapore special education (SPED) school context through the SLP at WGS. It highlights the initiative’s role in enhancing inclusivity, practical learning, and fostering key skills while addressing challenges in implementation. The SLP applies CBL theory and Kolb’s experiential learning model, incorporating community projects and reflection using Driscoll’s Model of Reflection. Data from observations, student journals, and teacher feedback were analyzed thematically to assess self-determination, social-emotional development, and community integration. The project engaged 79.5% of junior and senior students and 77.9% of high-support-needs students in tiered roles, in collaboration with four community partners. It strengthened community partnerships, integrated curriculum effectively, and provided authentic learning experiences. Feedback highlighted improvements in social-emotional skills, self- determination, and civic responsibility, though task suitability for students with high-support-needs requires further refinement. Building on 2024’s achievements, the SLP will continue in 2025 with a focus on sustainability and addressing identified challenges to enhance its impact further.